Front Cover: An Autophagy‐Disrupting Small Molecule Promotes Cancer Cell Death via Caspase Activation (ChemBioChem 24/2021). (10th August 2021) - Park, Sang‐Hyun; Shin, Insu; Kim, Gun‐Hee; Ko, Sung‐Kyun; Shin, Injae
Abstract : A novel autophagy inhibitor (autophazole, Atz), identified by cell‐based high‐content screening of an imidazole library, is reported. Autophazole is mainly internalized into lysosomes and disrupts their function, thereby leading to inhibition of autophagy. In addition, Atz induces LMP‐mediated caspase‐dependent apoptosis of cancer cells. We anticipate that Atz will be a useful chemical probe for elucidating details about the autophagic process and understanding the correlation between autophagy and apoptosis. More information can be found in the Full Paper by I. Shin et al.